Pengaruh Zakat Produktif Terhadap Pemberdayaan Ekonomi Mustahik Warga Aceh di Kota Depok (Studi Kasus Taman Iskandar Muda, Sukmajaya) - Sofian Muhlisin; Kholil Nawawi; Muhammad Khusairi Fathahillah (CV. ITTC INDONESIA, 2025)
This research investigates the impact of productive zakat on the economic empowerment of mustahik (zakat recipients) among Acehnese residents in Depok City, with a case study in Taman Iskandar Muda, Sukmajaya. The study aims to evaluate the effectiveness of productive zakat programs in increasing the economic independence of mustahik, analyze their role in reducing poverty, and identify the key factors influencing the success of such empowerment initiatives. Using a quantitative method with data collected through surveys, interviews, and documentation, the research reveals that productive zakat significantly contributes to improving income levels, business sustainability, and entrepreneurial spirit among the beneficiaries. Critical elements such as work ethic, business capital, training, and mentoring were found to influence the success of the programs. The findings suggest that productive zakat, when managed professionally through institutions like UPZ (Unit Pengumpul Zakat), has the potential not only to alleviate poverty but also to transform mustahik into muzakki (zakat payers), thus fostering long-term economic resilience within the community.